An analysis of the CT and CT angiogram findings of methamphetamine induced stroke in young adults (≤45 years) presenting to GSH Emergency department - Ngamolane, Aaron (Division of Radiology, 2023)
MMED Title: An analysis of the CT and CT angiogram findings of methamphetamine induced stroke in young adults (≤ 45 years) presenting to GSH emergency department. The recreational use of methamphetamine in the Republic of South Africa is on the rise accounting for 30% of patients admitted to addiction rehabilitation centres countrywide1 . In the Western Cape province alone methamphetamine is the commonly abused drug, detected in 44% of patients admitted for addiction rehabilitation2 . Methamphetamine is a risk factor for stroke especially in young adults, it is therefore important to determine key radiological features of methamphetamine related stroke for prompt and accurate differentiation from other stroke aetiologies. Study of stroke in this group of participants is of paramount importance as stroke is the second most common cause of death worldwide, responsible for 11.8% of all deaths after ischaemic heart disease (14.8%)3 . Stroke is also responsible for 4.5% of disability adjusted life years (DALYs)3 . The aim of the study was to determine whether stroke in young adults (≤ 45 years) exposed to methamphetamine can be differentiated from other stroke aetiologies on brain CT and CT angiogram. A cross-sectional retrospective study was performed in the department of radiology in Groote Schuur Hospital on brain CT and CT angiograms and their final reports from October 2012 to October 2020. All patients aged 45 years old or younger with clinical features of stroke and a history of methamphetamine or polysubstance abuse were included. Data collection tools were designed to suit inclusion criteriums and used as search keywords in the PACS for GSH. A re-read was done by the principal investigator as a second-year radiology registrar with limited neuroradiology experience guided by the study parameters outlined in the data collection tool. The obtained data was correlated with the finalized reports from each study. Our study has shown that in a group of young patients who admitted to using tik and who presented to the emergency room with clinical features of cerebral stroke, ischaemic infarct was found significantly more often than intracerebral haemorrhage. This study demonstrated that MCA territories were most frequently involved with occlusion of the M1 segments bilaterally. Radiologically loss of grey-white matter interface and a wedge-shaped appearance are the predominant patterns of radiographic presentation. This study has demonstrated that CT appearance of methamphetamine induced stroke does not differ from stroke patterns seen with traditional risk factors.